2015
DOI: 10.3791/52586
|View full text |Cite
|
Sign up to set email alerts
|

Probe-based Real-time PCR Approaches for Quantitative Measurement of microRNAs

Abstract: Probe-based quantitative PCR (qPCR) is a favoured method for measuring transcript abundance, since it is one of the most sensitive detection methods that provides an accurate and reproducible analysis. Probe-based chemistry offers the least background fluorescence as compared to other (dye-based) chemistries. Presently, there are several platforms available that use probe-based chemistry to quantitate transcript abundance. qPCR in a 96 well plate is the most routinely used method, however only a maximum of 96 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
(32 reference statements)
0
23
0
Order By: Relevance
“…We found a comparable level of reproducibility on this platform when using cards from the same lot ( Supplementary Fig. 1 ), but have observed considerable lot-to-lot variation 29 .…”
Section: Discussionmentioning
confidence: 54%
“…We found a comparable level of reproducibility on this platform when using cards from the same lot ( Supplementary Fig. 1 ), but have observed considerable lot-to-lot variation 29 .…”
Section: Discussionmentioning
confidence: 54%
“…RNA isolation methods were evaluated for maximum RNA yield and amplifiable miRNA levels. Isolation method efficiency was measured through RT‐qPCR analysis, as previous work has shown that UV spectrophotometry and other methods cannot precisely predict miRNA concentrations in the low concentrations observed in biological fluids . Consistent volumes of biological secretions from the same donor and donation were used, and elution volumes were normalized to 50 μL to allow for ease of comparison.…”
Section: Resultsmentioning
confidence: 99%
“…RNA extraction, cDNA synthesis, and preamplification were performed as previously described (10). Human Pool A v2.1 and B v3.0 Megaplex stem-loop RT Primers (Applied Biosystems) were used to produce cDNA.…”
Section: Mirna Profilingmentioning
confidence: 99%